Perancangan Interior Sekolah dan Pusat Informasi Mode “Arva School Of Fashion” di Surabaya - Sergio Jan Tonggi Soetedjo; Cok Gede Padmanaba; Diana Thamrin (Intra, 2015)
The Interior design of "Arva School Of Fashion" Fashion School and Information Center in Surabaya is done to fulfill the needs of facilities in order to accommodate the increasing number of students in the institution. Besides, this design is also done in order to support its new program by creating an education facility which serves as an educative protocol as well as a commercial bridge for student’s work to the society. There is an information center facility included in this design as a form of institute’s awareness of the mode world. Center of superiority is chosen as the concept of this design with the means of having arva school of fashion as the top notch in the mode field and be acknowledged on the national and international level.